Caring Environment Model in Emergency Services of Hospitals by Banyumas Public Perception (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Caring environment for providing service in the emergency departmentof the hospital becomes the need of the society. Caring environment has impact on the satisfaction, safety, and potential success of the services for the patients. The research aims at identifying the perception of society on caring environment as well as confirming the model of caring environment for providing emergency service in the hospital. This research employs descriptive exploration, involving 300 patients of emergency department from three hospitals in Banyumas. The analysis of decriptive data is conducted to categorize the perception of society on caring environment. The construct validity of caring environment is tested using confirmatory factor analysis. The result shows that the perceptions of society on caring environment in emergency department are good (86.3%) and fair (13,7 %). As the construct used to shape the model of caring environment has met the criteria of goodness of fit, involving: GFI; 0.96, RMSEA; 0.031, AGFI; 0,94; NFI;0,98; CFI;1, so it is revealed that the measurement model of caring environment for providing emergency service is fit. Moreover, all indicators are able to explain and support the model of caring environment for providing emergency services, involves; clean and comfortable room, complete facilities and equipments, and room safety. This finding could be the foundation for formulating the policy of caring quality improvement related to the aspect of caring environment for providing emergency services.